Metalworking at Hazor: A Long‐Term Perspective. Issue 1 (February 2014) - Yahalom‐Mack, Naama; Gadot, Yuval; Eliyahu‐Behar, Adi; Bechar, Shlomit; Shilstein, Sana; Finkelstein, Israel
Summary The temporal and spatial distribution of metal production remains from Hazor was used in this study to sketch the development of metalworking (bronze, iron and silver) at this important site. The remains attest to a long sequence of metalworking at Hazor, from the Middle Bronze Age through to the Iron Age, and significantly highlight the transition from bronze to iron production and the mode of bronze production after the transition had been completed.